Geogebra Application Utilization Training for Interactive and Innovative Mathematics Learning for Junior High School Teachers in Garut - Sumartini, Tina Sri; Noor, Yandhi Hendarsyah; Abdulah, Agus Herman; ., Rubiah; ., Agustina; ., Juniawati; Sugandi, Tatan; ., Yulkhaidir; Rosidah, Nani (Fakultas Kewirausahaan Universitas Garut, 2023)
This community service trained junior high school mathematics teachers in Garut to utilize Geogebra for interactive and innovative learning. The training, held on October 19, 2023, at IPI Garut, involved 30 teachers. Results showed a significant increase in teachers' understanding and skills using Geogebra, evidenced by improved pre-test to post-test scores and the quality of designed learning activities. Teachers also gained motivation and confidence to innovate. Despite suburban infrastructure challenges, the training was effective in equipping teachers to make mathematics learning more visual and engaging, boosting student interest and comprehension. Ongoing mentoring and infrastructure support are recommended.